2018
DOI: 10.1294/jes.29.1
|View full text |Cite
|
Sign up to set email alerts
|

Combined thickness of the uterus and placenta and ultrasonographic examinations of uteroplacental tissues in normal pregnancy, placentitis, and abnormal parturitions in heavy draft horses

Abstract: The combined thickness of the uterus and placenta (CTUP) and ultrasonographic images of uteroplacental tissues were investigated in 35 pregnant heavy draft horses in Months 7–12 of pregnancy. The mares were divided into three groups: those pathologically diagnosed as placentitis (placentitis group, n=3); those who had abortion, premature birth, or fetal malformation (abnormal group, n=7); and those who had no abnormal findings (normal group, n=25). In the normal group, CTUP increased as pregnancy progressed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
3
1
2
Order By: Relevance
“…In the present study, the CTUP was between 6 and 9 mm in the last 2 months of gestation. These values are lower than the CTUP reported by Kimura et al [19] in heavy draft horses (approximately 13 mm) and Spanish Purebred mares (10.45 mm) on day 300 of gestation [34]. The CTUP values observed in the present study were close to those in Thoroughbred horses (range 7-10 mm on day 330 of gestation) [12,33].…”
Section: Discussioncontrasting
confidence: 52%
“…In the present study, the CTUP was between 6 and 9 mm in the last 2 months of gestation. These values are lower than the CTUP reported by Kimura et al [19] in heavy draft horses (approximately 13 mm) and Spanish Purebred mares (10.45 mm) on day 300 of gestation [34]. The CTUP values observed in the present study were close to those in Thoroughbred horses (range 7-10 mm on day 330 of gestation) [12,33].…”
Section: Discussioncontrasting
confidence: 52%
“…The CTUP (mm) was elevated among gestational ages, which is in accordance with some studies [ 15 , 17 , 28 , 29 ], as all previous studies demonstrated that this elevation is within the normal values of the combined thickness and revealed that the placental tissue was functional and efficient during different stages of pregnancy [ 30 ]. Any abnormalities in CTUP thickness could adversely affect the maintenance of pregnancy and therefore lead to placental separation [ 31 ] and placentitis [ 32 ]. As fetal growth depends mainly on placental growth and development [ 33 , 34 ], a study found that CTUP remained within constant levels, it did not change.…”
Section: Discussionmentioning
confidence: 99%
“…Os lábios vulvares devem ser cheios e firmes e se encontrarem na linha media, sendo que 80% ou mais da comissura vulvar está abaixo do assoalho pélvico. Se o fechamento vulvar é incompetente, a aspiração de ar e a contaminação fecal podem ocorrer (KIMURA et al, 2018).…”
Section: Fatores Predisponentesunclassified
“…Além disso, os protocolos de tratamento utilizados atualmente são empíricos devido ao escasso conhecimento sobre a patogênese da doença (KIMURA et al, 2018).…”
Section: Introductionunclassified